Supplement levels and functional oils to replace virginiamycin for young bulls during early dry season on grasslands and finishing phase in feedlot systems - Renesto, Diego M. [UNESP]; Hoffmann, Alvair [UNESP]; Araújo, Tiago L. R. [UNESP]; Delevatti, Lutti M. [UNESP]; Leite, Rhaony G. [UNESP]; Ribeiro, José L.; Romanzini, Eliéder P. [UNESP]; Barbero, Rondineli P.; Reis, Ricardo A. [UNESP] (Instituto Nacional de Investigacion y Tecnologia Agraria y Alimentaria (INIA), 2021)
Aim of study: To assess the effects of replacing virginiamycin (VM) by functional oils (FO) from castor beans and cashew nut on beef cattle system during the early dry season (Experiment I) and during the finishing phase were evaluated the historical effect, keeping the treatments and methods intact (Experiment II). Area of study: These experiments were conducted at the Forage Crops and Grasslands section of São Paulo State University, “Julio de Mesquita Filho” (Unesp–Jaboticabal, São Paulo, Brazil). Material and methods: Two supplementation levels combined with two additives (four treatments in total) were evaluated: LSVM, low supplementation (0.3% body weight [BW]) with VM; LSFO, low supplementation (0.3% BW) with FO, HSVM, high supplementation (0.6% BW) with VM, and HSFO, high supplementation (0.6% BW) with FO. In both experiments, the experimental design was completely randomized with a 2 × 2 factorial arrangement (supplementation levels × additives). Main results: In Exp. I, the additive effect of VM provided greater average daily gain (ADG, p=0.02), higher supplementation level resulted in higher ADG (p=0.04) and the greatest crude protein apparent digestibility (p=0.002). However, no effects were observed between supplementation levels, additives, and interactions (p≥0.11) on voluntary intake and ruminal parameters. In Exp. II, LSVM treatment resulted in lower dry matter intake (p=0.04). Animals maintained on LSFO during the early dry season exhibited lower carcass yield (p=0.004). Research highlights: FO can be used to replace VM in beef cattle diet during the finishing phase in the feedlot without altering animal performance.
Keywords: Additional beef cattle; Cardanol; Cardol; Cashew nut; Castor beans; Organic additive; Ricinoleic acid